PROBLEMATIKA KURIKULUM MERDEKA PADA SEKOLAH DASAR - Nasution, Riski Ananda; Ritonga, Masrianti; Asfiati, Asfiati; Harahap, Sery Bulan (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The Independent Curriculum, which is a new policy in education in Indonesia, aims to design learning that is flexible and independent to the needs of students at school. However, in implementing the independent curriculum, there are still various challenges in elementary schools. Therefore, this study aims to identify problems in the implementation of the Independent Curriculum in elementary schools, which are seen from the aspects of teacher readiness, facilities, understanding of curriculum concepts, and parent participation. The research uses a qualitative method with a literature study approach. The results show that the lack of teacher training, limited resources, and differences in understanding between stakeholders are the main obstacles. In addition, with many school conditions, such as those in remote areas, it adds to the complexity of implementation. This study suggests improving training, strengthening technical support, and increasing collaboration between schools and the government in maximizing the effectiveness of the Independent Curriculum program in elementary schools.